2021
DOI: 10.15258/sst.2021.49.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Blend wheat AL-type hybrid and using SSRs to determine the purity of hybrid seeds

Abstract: Heterosis is a promising approach to increase wheat yield from a limited planting area. In this study, a fine quality restorer line 99AR144-1 and three stable male sterile lines, AL18A, AL36A and AL20A, were assigned as male and female, respectively. Seeds of the wheat line 99AR144-1 and three male sterile lines were mixed according to different proportions and then planted at an experimental farm at the Xinjiang Academy of Agri-Reclamation Sciences from 2013 to 2016. When the mixed sowing ratios of combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…New strategies for cost-effective hybrid seed production, e.g. blending (Nie et al 2021), apomixis (Lawit 2012), or doubled haploidy (Pazuki et al 2018), are being explored for a long time, but have not reached the stage of commercial exploitation for hybrid seed production in many species. Recently, Nie et al (2021) reported that blends of restorer and male sterile lines (AL-type cytoplasmic male sterile lines), mixed in different proportions, can result in a significant increase in hybrid seed production in wheat, though maintaining the desired genetic purity of the hybrid seed remains an issue to be resolved.…”
Section: Hybrid Seed Productionmentioning
confidence: 99%
“…New strategies for cost-effective hybrid seed production, e.g. blending (Nie et al 2021), apomixis (Lawit 2012), or doubled haploidy (Pazuki et al 2018), are being explored for a long time, but have not reached the stage of commercial exploitation for hybrid seed production in many species. Recently, Nie et al (2021) reported that blends of restorer and male sterile lines (AL-type cytoplasmic male sterile lines), mixed in different proportions, can result in a significant increase in hybrid seed production in wheat, though maintaining the desired genetic purity of the hybrid seed remains an issue to be resolved.…”
Section: Hybrid Seed Productionmentioning
confidence: 99%
“…In order to make hybrid wheat seed production easy and cost-effective, the blend hybrid seed production method has been proposed which maximizes hybrid seed production with cost reduction. A recent study has reported that a blending of 6 to 8% restorer line seeds with the seed parent seed increased the yield of mixed hybrid seed production with higher purity (Nie et al 2021).…”
mentioning
confidence: 99%